Transfer Pricing and Taxation Dispute Resolution - Machfud Sidik (LPPM-STPI, 2021)
The role of MNEs in world trade is increasing drastically from time to time. Tax disputes, especially regarding transfer pricing between taxes and MNEs, have become an international issue. The solution to this dispute requires a balance of interests between MNEs and taxes. The growth of MNEs presents a complex taxation problem for both the tax authorities and the MNEs themselves as taxation varies between countries. These problems arise mainly from the practical difficulties, both for MNEs and taxes, in determining the income and expenses of companies or forms of business that are part of the MNE group that must be taken into account in the activities of each country, especially the activities of the integrated MNE group. Transfer pricing, for tax purposes, is the price of intercompany transactions that occur between businesses. The transfer pricing process determines the amount of income earned by each party from the transaction. Taxpayers and taxes relate exclusively to transactions called controlled transactions, and have no direct impact on independent party transactions, which are called uncontrolled transactions. Transactions, in this context, are defined broadly, and include sales, licenses, leasing, services and interest. Tax authorities need attention for greater attention to global trade instruments by MNE groups. Indonesia has formulated provisions related to transfer pricing since 1984 when the first tax reform was introduced. However, the technical guidelines to meet the principles that will be implemented by the new tax auditors are in 2010 and are implemented effectively in 2011 and the following period through Law No. 11/2020 and the 2021 KUP Bill. There are various challenges in implementing the existing transfer pricing provisions. currently, especially related to payments for intangible uses, payment of interest on debt to equity, payments for intragroup services which are basically regulated in the technical provisions of transfer pricing and inspections related to selling prices and buying prices for intra-group trading are basically regulated in domestic regulations. Indonesia. In addition, in the transfer pricing test, there are considerable disputes which are technical issues such as (i) the selection of transfer pricing testing methods (ii) the selection of comparative data (iii) the audit process is not appropriate. Along with the development of cross-border financial institutions, developments regarding transfer pricing and BEPS are expected to increase. It is therefore very important that Indonesian tax oversight pay attention to skilled personnel to cope with the increase brought about by global instruments by MNE groups.